The Effect of Environmental Concern and Attitude of Toward Green Brand on Green Purchase Intention: Evidences in Milenial Generations in Jakarta - Adiputra, I Gede; Nataherwin,; Aoleria, Kezia (Archives of Business Research, 2023)
The purpose of this research is to determine whether Attitude Toward Green Brand and Environmental Concern have an important role in the purchase intention of natural cosmetic ingredients in Jakarta. It is hoped that this research can provide clarity about the role of Attitude Toward Green Brand and Environmental Concern in the intention to buy cosmetics made from natural ingredients as well as fill in the gaps in research on consumer buying intentions for cosmetics made from natural ingredients which are relatively minimal among practitioners and academics, especially with the impact of the COVID pandemic. -19 by means of using different variables. This study used a survey method, with data collection through a questionnaire. Data for this study were collected from 200 respondents using a convenience sampling technique, then the data were analyzed using SMARTPLS. According to the findings of this study, Attitude Toward Green Brand and Environmental Concern have a positive and significant impact on purchase intention of Sensatia Botanicals skincare products in Jakarta. It is hoped that this research can fill the research gap regarding consumer purchase intentions for organic ingredients which are still relatively minimal among practitioners and academics, especially with the impact of the COVID-19 pandemic.